2021
DOI: 10.1186/s12889-021-10493-6
|View full text |Cite
|
Sign up to set email alerts
|

Citizen science as a tool for arboviral vector surveillance in a resourced-constrained setting: results of a pilot study in Honiara, Solomon Islands, 2019

Abstract: Background Recent arboviral disease outbreaks highlight the value a better understanding of the spread of disease-carrying mosquitoes across spatial-temporal scales can provide. Traditional surveillance tools are limited by jurisdictional boundaries, workforce constraints, logistics, and cost; factors that in low- and middle-income countries often conspire to undermine public health protection efforts. To overcome these, we undertake a pilot study designed to explore if citizen science provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Also, in the same program, households received feedback to take specific actions to manage mosquito breeding sites (Suwanbamrung et al, 2018). Also, facilitated engagement between citizens and scientists was reported in different programs and countries (Lwin 2017;Parra et al 2020;Craig et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, in the same program, households received feedback to take specific actions to manage mosquito breeding sites (Suwanbamrung et al, 2018). Also, facilitated engagement between citizens and scientists was reported in different programs and countries (Lwin 2017;Parra et al 2020;Craig et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Also, pilot projects were described in the Solomon Islands and in Rwanda, aiming to identify the opportunities and challenges to establish citizen science-based programs in these areas (Murindahabi et al 2019;Craig et al 2021). The citizen science engagement in Honiara, Solomon Islands, showed potential to upscale capacity for mosquito data collection locally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of iNaturalist for detecting vector species was also verified in Europe, North America, North Africa and the Middle East [19], and the results indicated that the iNaturalist platform could complement existing vector surveillance data. Citizen science initiatives on mosquito surveillance are also emerging in tropical countries and areas where dengue and malaria are endemic [22,56,57], and ethical issues were discussed in a community-based program in Nicaragua and Mexico [58]. As ethical discussions underlining communitybased research have shown, researchers should ensure that individuals and communities have the autonomy to monitor and control the vectors in their properties and have a safe space for a dialogue focusing on mutual respect and community health [58].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the field of citizen science has aroused increasing interest in various areas of health and biomedical sciences such as epidemiological monitoring, health behavior surveillance, environmental health study, molecular biology, and genomics (for more information, see [15][16][17][18][19][20][21]). However, to date, relatively less contribution has been made to this area compared to well-established areas of citizen science such as ecology, conservation, earth sciences, and astronomy [22].…”
Section: Introductionmentioning
confidence: 99%